N-2 activation on Al metal clusters: catalyzing role of BN-doped graphene support - Kumar, Deepak; Pal, Sourav; Krishnamurty, Sailaja (Physical Chemistry Chemical Physics, 2016)
The successful sustenance of life demands an ambient abiotic process for N-2 activation and dissociation. The Bosch-Haber process remains the only abiotic and synthetic means for N-2 activation and its fixation. Metal nanoclusters have been recently reported for activating molecular nitrogen. Interestingly, the metal clusters explored so far for N-2 activation are free clusters and, hence, are practically not applicable by experimental chemists. Using density functional theory (DFT) based methodology, we propose a potential catalytic system for di-nitrogen activation, viz. supported Al clusters. Al clusters supported on BN doped graphene sheets are seen to activate N-2 molecule with a red shift in the N-N stretching frequency up to 874 cm(-1) with activation barriers as low as 1.14 eV.